2018
DOI: 10.1101/331793
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

General Regulatory Factors control the fidelity of transcription by restricting non-coding and ectopic initiation

Abstract: The fidelity of transcription initiation is essential for accurate gene expression, but the determinants of start site selection are not fully understood. Rap1 and other General Regulatory Factors (GRFs) control the expression of many genes in yeast. We show that depletion of these factors induces widespread ectopic transcription initiation within promoters. This generates many novel non-coding RNAs and transcript isoforms with diverse stability, profoundly altering the coding potential of the transcriptome. E… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…For mRNAs, we used the annotations in Challal et al (). For the 5′ and the 3′ end of mature snoRNAs, we used the annotations in Xu et al ().…”
Section: Methodsmentioning
confidence: 99%
“…For mRNAs, we used the annotations in Challal et al (). For the 5′ and the 3′ end of mature snoRNAs, we used the annotations in Xu et al ().…”
Section: Methodsmentioning
confidence: 99%
“…A combination of both in vivo studies (Ganapathi et al, 2011;Hartley and Madhani, 2009;Kubik et al, 2018;Tsankov et al, 2011;van Bakel et al, 2013;Yan et al, 2018;Yarragudi et al, 2004) and in vitro reconstitutions indicated that these 6 Senior author 7 These authors contributed equally. This organization is important for transcription fidelity as mutants with impaired array phasing show aberrant transcription initiation (Challal et al, 2018;Hennig et al, 2012;Kubik et al, 2019;Pointner et al, 2012;Smolle et al, 2012). Throughout eukaryotes, phased arrays are prominent at active promoters.…”
mentioning
confidence: 99%